Chest x ray films from construction workers: International Labour Office (ILO 1980) classification compared with routine readings. Issue 12 (December 1992) - Albin, M; Engholm, G; Fröström, K; Kheddache, S; Larsson, S; Swantesson, L
Abstract : The extent of agreement between International Labour Office (ILO) and clinical readings of chest x ray films from construction workers was studied. From a survey of 5898 workers 258 subjects with a profusion of small opacities of > or = 1/1 and a stratified sample of subjects with profusion < 1/1 were selected. Only 41% of the films classified as ILO profusion category > or = 1/1 were clinically recorded as non-normal for the parenchyma. The proportion of films recorded as pneumoconiotic (or possibly so) was especially low for irregular opacities (22%), but increased with the profusion category (both rounded and irregular) as well as with the size of rounded opacities (p 3/11, q 12/25, r 3/4). Only with the profusion category > or = 2/1 were most of the films recorded as pneumoconiotic. The specificity and sensitivity were highest in the geographical areas where a few clinical readers had assessed many films each. The proportion of false negative clinical reports was low for circumscribed pleural thickening of the chest wall (9%) and diaphragmatic pleural thickening (6%). For calcified pleural changes and for the combination of diffuse pleural thickening and obliteration of the costophrenic angle, false negative reports were absent. The present study shows an unsatisfactory sensitivity for clinical compared with ILO readings as a means for screening the parenchyma of workers with a risk of pneumoconiosis.